DYNAMICS OF THE PRIVATE ISLAMIC COLLEGE EDUCATION SYSTEM IN INDONESIA: A SYSTEMATIC REVIEW - Rodin, Rhoni; Asha, Lukman; Warlizasusi, Jumira; Fakhruddin, Fakhruddin (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2025)
This article aims to examine the dynamics of the education system in Private Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Swasta/PTKIS) in Indonesia through a systematic review approach. The study was conducted by identifying, evaluating, and synthesizing a range of scholarly articles, policy reports, and relevant documents published over the past ten years. The method involved searching academic databases using specific keywords, selecting documents based on inclusion and exclusion criteria, and conducting thematic analysis of key emerging issues. The findings indicate that PTKIS in Indonesia face various challenges, including institutional governance, funding, academic quality, and graduate competitiveness. On the other hand, several innovations and strategic initiatives have been undertaken by PTKIS to improve educational quality, expand access, and strengthen collaboration with external parties. This review concludes that strengthening the PTKIS education system requires a holistic approach encompassing regulatory reform, sustainable financing, human resource development, and digital transformation to meet the demands of the times.